2015
DOI: 10.14260/jemds/2015/1282
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Refractive Error With Corneal Curvature of the Eye in Adult Subjects With Refractive Error

Abstract: BACKGROUND:The second most common reason for blindness worldwide is refractive error. Not only is the global burden of refractive error very high, but also increasing every day. A number of associated serious complications and the various modes of treatment aspect of the refractive errors, warrants the necessity to explore the various factors that have impact on them. The present study was done with the purpose of establishing the relation of refractive error with corneal curvature of the eye in adult subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…14 Arora et al, in 2015, studied 1000 eyes of 500 candidates with different types of refractive errors. 15 The mean age of our study subjects was 28.1± 5.79 years, with a range from 18 to 40 years. In contrast, the study by AlMahmoud et al included patients with a mean age of 40±10 years, ranging from 19 to 84.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…14 Arora et al, in 2015, studied 1000 eyes of 500 candidates with different types of refractive errors. 15 The mean age of our study subjects was 28.1± 5.79 years, with a range from 18 to 40 years. In contrast, the study by AlMahmoud et al included patients with a mean age of 40±10 years, ranging from 19 to 84.…”
Section: Discussionmentioning
confidence: 97%
“…12,13 The correlation between refractive error and corneal parameters has been previously studied in different regions and populations. 3,[14][15][16] The purpose of this work is to find out if there is any correlation between corneal parameters (namely, central corneal thickness and corneal power) and the refractive error in the myopic adult Egyptian population.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although, this study did not find any correlation between spherical equivalent and corneal curvature, some studies revealed that the spherical refractive error has statistically highly significant positive correlation with corneal curvature but other studies reached a similar conclusion that no significant correlation was present between spherical refractive error and corneal curvature. 6,10,[15][16][17] Several reasons may account for these differences in results from different studies, such as differences in age groups, refractive error ranges, sample size, populations, ethnicities, statistical power of the studies and various methods of measurement of various ocular parameters. 6…”
Section: Discussionmentioning
confidence: 99%
“…5 The prevalence of refractive errors especially myopia is currently attracting worldwide attention as many recent studies report dramatic increases over the last 20 years. 6 Anterior corneal curvature expressed in radii (mm) is important for contact lens fitting and management, ocular aberration analysis, corneal refractive surgery as well as diagnoses and management of corneal pathological conditions. 6 A cornea that is too curved (radii are abnormally small) is found in keratoconus and a cornea that is too flat is found in conditions such as cornea plana, which is a rare bilateral condition associated with severe refractive errors, cataracts and coloboma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation